Chapter 12: Decompressive Craniectomy: Long Term Outcome and Ethical Considerations - Kwan, Kevin; Schneider, Julia; Ullman, Jamie S. (Frontiers in Neurology, 2019)
Decompressive craniectomy (DC) for the treatment of severe traumatic brain injury has been established to decrease mortality. Despite the conclusion of the two largest randomized clinical trials associating the effectiveness of decompressive craniectomy versus medical management for patients with traumatic brain injury, there is still clinical equipoise concerning the usefulness of DC in the management of refractory intracranial hypertension. Primary outcome data from these studies reveal either potential harm or that decreased mortality only leads to an upsurge in survivors with severe neurological incapacity. In this chapter, we seek to review the results of the most recent clinical trials, highlight the prevailing controversies, and offer potential solutions to address this dilemma.